Blowdown Heat Recovery Using Hybrid Fuel Drying System in Biomass Power Plant - Somchart Chantasiriwan (Chemical Engineering Transactions)
A hybrid fuel drying system is a system that uses both a steam dryer and a flue gas dryer for fuel drying. This system is particularly suitable for a biomass power plant because its fuel may have a high moisture content. The previously proposed hybrid drying system uses extracted steam to operate the steam dryer. Exhaust vapor from the steam dryer is used for the heating of combustion air in an air preheater. Flue gas dryer is installed at the outlet of boiler to reduce flue gas temperature to 120 (C. In this paper, it is proposed that steam requirement of steam dryer could be met by using flash steam from blowdown heat recovery system. A comparative analysis of two power plants is carried out in this paper. The reference power plant consumes 11.23 kg/s of biomass fuel having 50 % moisture content. The boiler of this power plant supplies 26.74 kg/s of steam at pressure 6.0 MPa and temperature 497.5 (C. The blowdown rate is 4 %, and there is no blowdown heat recovery. The net power output of the reference power plant is 25.0 MW. The modified power plant is integrated with the proposed heat recovery system. It consumes the same amount of fuel, and uses the same boiler. The blowdown heat recovery system supplies flash steam at pressure 250 kPa to steam dryer. The boiler supplies flue gas at temperature 143.7 (C to flue gas dryer. Both dryers are used to reduce fuel moisture content from 50 % to 47.4 %, and increase combustion air temperature from 25 (C to 37.2 (C. As a result of drier fuel and hotter air, the boiler generates 26.84 kg/s of steam at temperature 525.4 (C. The net power output of the modified power plant is 26.02 MW, which is 4.1 % higher than that of the reference power plant. Furthermore, it can be shown that the proposed system is economically attractive.